THE DYNAMICS OF OFF-AXIS PLUME-RIDGE INTERACTION IN THE UPPERMOST MANTLE - Kincaid C.; Schilling J.G.; Gable C. (My University, 1996)
Two decades of geochemical and geophysical observations have led to the plume channel model whereby buoyant, off-axis mantle plumes feed and interact with diverging plates at mid-ocean ridge axes which act as sinks of upper mantle material. Here we present results from two-dimensional (2-D) numerical experiments which incorporate the essential physics and fluid dynamic aspects of the plume-ridge-upper mantle system in order to test the feasibility of this plume-ridge interaction model. Specifically, experiments test the relative importance of physical effects such as strong viscosity variations and thermal and chemical buoyancy forcing in plume-ridge dynamics. Results indicate that both transient and steady-state connections may be established between off-axis plumes and ridges for a range of realistic mantle conditions. The presence of a strongly sloping rheological boundary layer (RBL) is a necessary condition for long-term communication between an off-axis buoyant upwelling and a spreading ridge. The flux of buoyant material to the ridge is also shown to increase with increasing plume-to-mantle density contrast, decreasing plume viscosity and smaller plume-ridge separation distances. Plume-ridge interaction regimes are defined based on the competing effects of plate-driven and buoyancy-driven flow. Thermal erosion of the viscous lithosphere strongly inhibits long-term plume-ridge interaction by enhancing the plates ability to deflect the plume, both head and conduit, away from the ridge axis.